P75 Evaluation of a complex home ventilation population before and after the advent of COVID-19 in the UK. (11th November 2022) - Ward, K; Weir, M; Campbell, L; Faulkner-Byrne, K; Jordan, J; Hughes, A; Angus, RM; Chakrabarti, B; Parker, R; Nwosu, N; Plant, PK; Manuel, A
Abstract : Introduction: Although formal patient registries in complex home ventilation have long been recommended 1, recent review found few centres maintain accurate records of activity 2 . However, the ability to identify patient requirements such as dependence on home ventilation is essential for appropriate care and service commissioning 2 . In the local setting, the regional ventilation service established a combined risk assessment and treatment registry in 2018. The Pro-VISO tool was developed with examples from national network. Four aspects of treatment risk were included (ventilation, V; interface, I; secretions, S, and oxygen, O) alongside diagnosis, equipment and settings. This study aimed to examine the home ventilation registry for possible change in cohort characteristics before and after the advent of COVID-19 in the UK. Methods: Retrospective analysis of patient registry for ventilation method (invasive, non-invasive), ventilator dependence 2 (>14 h/night) and survival was undertaken. Comparison was made of three timepoints, one preceding and two after the first UK wave of COVID-19. Subgroup analysis was performed for mortality amongst non-invasive and invasive users with and without ventilator dependence. Results: Data was available for timepoints T1 (26.2.20), T2 (3.3.21) and T3 (7.6.22). Total caseload at T1, T2 and T3 respectively was n=1042/1094/1139 ( figure 1 ), mean age 59.3 (SD 16.0)/58.9 (SD 16.2)/59.0 (SD 15.8), male 51.7/52.7/52.3%. Dynamic changes to the patient population were seen, with new referrals (T1–2, n=182/T2–3, n=285) and deaths (T1–2, n=132/T2–3, n=234). Subgroup analysis revealed an association between non-invasive ventilator dependence and mortality in T2–3 (n=19/52, 36.5%; p<0.0005). There was no association with mortality for this subgroup at T1–2, or any other group at any time. Conclusions: The apparent association between home non-invasive ventilator dependence and increased mortality in the second year of COVID-19 in the UK warrants investigation of unmet need in this patient group, compared with the invasively ventilated. Targeted review is planned in the local setting, facilitated by utilisation of home ventilation registry as a method of population surveillance. References: Lloyd-Owen SJ, et al . Patterns of home mechanical ventilation use in Europe: results from the Eurovent survey. ERJ 2005; 25 : 1025–1031. Allen M. Respiratory Medicine: GIRFT Programme National Specialty Report . London: GIRFT, 2021.